Práticas avaliativas na Educação de Jovens e Adultos em escolas da rede pública de Fortaleza-CE: fator de inclusão escolar - Macedo, Sheyla Maria Fontenele (2008)
The present research aims to supply theoretical subsidies for reflection in the field of the educational evaluation facing the practices adopted in the education of youth and adults in the initial series of basic education and if these benefit or not the exercise of the education right, focused on the permanence aspect, access and scholar inclusion of the pupil. So, the “weaving” was disclosed in this essay among the historical conceptions of the evaluation in the scene of youth and adults education, of the individual and social subjectivity that supports the schooling culture formation, through its speech, dialog aspect, social relations and evaluation concerning the adopted pedagogic practice in YAE. The topic might be translated into the following question: the evaluative practice adopted in the scene of the and Adults and Youth Education in Public Schools of Fortaleza suggests the permanence process of the pupil in the school, corroborates for its inclusion in the heart of society and then, in the exercise of education right? The work is based on bibliographical, documental and realistic experiments research. Through the experiments, we tried to adopt, as instrumentals, the commonly applied survey to ten percent of the MUNICIPAL public school teachers and the focused group, applying with 06 students from Regional VI schools, where we tried to point the “modus operandi” of the evaluative practice concerning the possibility of compliance of the social role of including the pupil in the school and in the society.Th e act of digging and searching the thematic of the evaluation as a pedagogical practice in Youth and Adult Education allows the problem to occupy a significant epistemologic space, mainly when we refer to the several variable aspects that cross the work developed by the teacher in the construction of a humanized evaluative practice. After an excursion on the designated conceptions, we can announce it as one of the main final considerations, which the act of evaluating is tied to the formation of the internalized “habitus” culturally